THE EFFECT OF USING SHOPEE PAYLATER ON IMPULSE BUYING WITH HEDONIC VALUE AS A MEDIATION VARIABLE - Eni Setiawati; I Gede Nandya Oktora P (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Paylater is a type of electronic credit payment that makes it easier for consumers to make payments when shopping. The convenience of the payment system is one of the supporting factors for the development of e- commerce and impulse buying. Shopee is an application that provides a paylater feature as a payment system. This research aims to explain the influence of using Shopee paylater on impulse buying which is mediated by hedonic values in Generation Z people who use Shopee. This research was conducted in Denpasar City with a total sample of 120 respondents using a questionnaire tool. The sample was determined using a non-probability sampling model with purpose sampling technique. The data analysis techniques used are the classic assumption test, path analysis using SPSS for Windows tools, the Sobel test and the VAF test. The results of the analysis show that all hypotheses are accepted. Using Shopee Paylater has a positive and significant effect on impulse buying, using Shopee Paylater has a positive and significant effect on hedonic value, hedonic value has a positive and significant effect on impulse buying, and hedonic value is able to partially mediate the influence of using Shopee Paylater on impulse buying.